Annealing effect on the structural and optical properties of embedded au nanoparticles in silicon suboxide films - Chan, K.W.; Aspanut, Zarina; Dee, C.F.; Muhamad, M.R.; Rahman, S.A.; Goh, B.T. (2012)
Au/SiOx nanocomposite films have been fabricated by co-sputtering Au wires and SiO2 target using an RF magnetron co-sputtering system before the thermal annealing process at different temperatures. The structural and optical properties of the samples were characterized using X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), optical transmission, and reflection spectroscopy. XPS analysis confirms that the as-prepared SiOx films are silicon-rich suboxide films. FESEM images reveal that with an increase in annealing temperature, the embedded Au NPs tend to diffuse toward the surface of the SiOx films. In IR spectra, the intensity of the Si-O-Si absorption band increases with the annealing temperature. Optical spectra reveal that the position and intensity of the surface plasmon resonance (SPR) peak are dominated by the effect of the inter-particle distance and size of the Au NPs embedded in the SiOx films, respectively. The SPR absorption peak shows the blue-shift from 672 to 600 nm with an increase in annealing temperature. The growth of silica nanowires (SiOx NWs) is observed in the film prepared on a c-Si substrate instead of a quartz substrate and annealed at temperatures of 1000 degrees C. (C) 2012 Elsevier Ltd. All rights reserved.